Changes implemented in the work environment of nurses in the COVID-19 pandemic - José Luís Guedes dos Santos; Fernando Henrique Antunes Menegon; Gustavo Baade de Andrade; Etiane de Oliveira Freitas; Silviamar Camponogara; Alexandre Pazetto Balsanelli; Alacoque Lorenzini Erdmann (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to describe the changes implemented in the work environment of nurses in university hospitals considering the COVID-19 pandemic. Methods: this qualitative and descriptive research was developed from an online survey with 75 nurses from three Brazilian university hospitals. Data processing occurred through textual analysis with the aid of software IRAMUTEQ. Results: five semantic classes were obtained: Organization of units for exclusive care of patients with COVID-19; Adaptations in the use of personal protective equipment; Physical structure adaptation; Care flow institution; Increased number of beds and training courses. Final considerations: the results show the effort of healthcare and nursing professionals/managers in the development of structural adaptations and reorganizations of care processes, in the hospital context, to respond with quality and efficiency to the demands arising from the COVID-19 pandemic.